The making of international law - Boyle, Alan E.; Chinkin, Christine 1949- (Oxford University Press, 2007)
Studying the principal negotiating processes and law-making tools by which international law is developed, this book looks at the UN, diplomatic conferences, codification bodies, NGOs, and courts in identifying the processes, participants and instruments used in the making of international law.
Keywords: Internationaal recht; Internationale betrekkingen; Internationale Politik; Internationales Recht; International law; International agencies; International courts; Treaties; Gesetzgebung; Kodifikation